Report of the Workshop on Status and Trends of Western North Atlantic Right Whales - Int, IWC (J. Cetacean Res. Manage., 2020)
The meeting was held at the Northeast Fisheries Science Center (NEFSC), Woods Hole, Massachusetts, USA from 24-27 October 1999.